PERANAN MODAL SOSIAL DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA BENDAR, KECAMATAN JUWANA, KABUPATEN PATI - SUPRATIWI, SUPRATIWI (Program Magister Ilmu Politik, Universitas Diponegoro, 2012)
AbstractThe research was motivated by a policy of regional autonomy, which necessitates thedecentralization to the village level. With so expected economic empowerment of rural communitiesthat have an impact on the independence of rural communities. This is as seen in villages Bendar,Juwana district, Pati regency.Therefore, the formulation of the problem in this study was to determine how the role of socialcapital in rural Bendar so that it can improve welfare. The method used in this study was a descriptivequalitative techniques of data collection through interviews and literature review.The results showed that there were several social capital in Bendar village has a very largerole in improving welfare in rural Bendar. Social capital, which is the first form of social trust (socialaspects). Second, the values of hard work and perseverance (cultural aspects), the third form ofeconomic organization formed by the community (economic aspects). Fourth, the role of women.Keywords: Social Capital, welfare